Technical approaches to evaluate the surfactant-enhanced biodegradation of biodiesel and vegetable oils - Montagnolli, R. N. [UNESP]; Cruz, J. M. [UNESP]; Moraes, J. R. [UNESP]; Mendes, C. R. [UNESP]; Dilarri, G. [UNESP]; Lopes, P. R.M. [UNESP]; Bidoia, E. D. [UNESP] (Springer Nature, 2019)
This research compared the effects of biosurfactant on the biodegradation of biodiesel and vegetable oils while validating two conceptually diverging methodologies. The two experimental setups were successfully modeled towards the effects of biosurfactants during biodegradation. We established the equivalence of both methodologies from the data output. As expected, the biosurfactants caused an increased oil uptake, thus increasing biodegradation performance. Cooking oils were favored by the microbial consortium as a carbon source when compared with biodiesel fuel, especially after use in food preparation. However, we found that biodiesel substrate standout with the highest biodegradation rates. Our results might indicate that a rapid metabolic change from the original compound initially favored biodiesels during the assimilation of organic carbon for a set specialized microbial inoculum. The data output was successfully combined with mathematical models and statistical tools to describe and predict the actual environmental behavior of biodiesel and vegetable oils. The models confirmed and predicted the biodegradation effectiveness with biosurfactants and estimated the required timeframe to achieve satisfactory contaminant removal.
Keywords: Biodegradation kinetics; Bioremediation; Colorimetric; Individual moving range chart; Mathematical modeling; Respirometric